Optimasi Proses Pembuatan Alat Bantu Mesin Gerinda Tangan: Efisiensi Waktu, Biaya, dan Kinerja - Irawan, Benny Haddli; Nugraha, M Affan; Hakim, Rahman (Jurnal Teknologi dan Riset Terapan (JATRA), 2023)
Hand grinding machine is a crucial tool in the manufacturing industry for cutting and smoothing various materials, including large-sized plates. This study aims to design and create an auxiliary tool for hand grinding machines to facilitate the process effectively. The research methodology involves design planning, material collection, cutting, and assembly. Evaluation of time and cost is also conducted. The results indicate that the auxiliary tool was successfully constructed according to the design with slight increases in time and cost. Experiments demonstrate that the tool enhances efficiency in cutting large plates. In conclusion, this auxiliary tool effectively improves productivity and efficiency in plate cutting, providing a solution for manufacturing industries requiring swift and accurate plate processing.